Expressão de raiva e desempenho motor: um estudo comparativo com adolescentes praticantes e não praticantes de esportes - Tasca, Layane Castiglioni (2012)
Adolescence is the stage that highlights the transition between childhood and adult life and it is characterized by alterations in several levels (physical, mental and social). It represents a process of distancing of behavioral forms for the individual. It's in the process of changing in adolescence that the emotions are evidenced. This research aimed to investigate the levels of limited aggressiveness to impulsive component anger and the motor performance of adolescents who practice and also who do not practice sports. 401 adolescents aged between 14 and 16 years were part of the study and they were enrolled in elementary and high school in Maringá-Pr. The evaluation of motor performance went through PROESP-BR test, extracted from the Manual of Norms, Tests and Measures Application and Criteria of Evaluation (GAYA, et. Al., 2012) for children and adolescents aged between 7 and 17 years. The aggressiveness through impulsive component anger was evaluated by State-Trait Anger Expression Inventory (STAXI) of Spielberger (1927), translated and adapted by Biaggio (2003), for adolescents aged from 13 years on. The results indicated that, among the subscales of players and non-players of sports, only the temper subscale revealed a disparity of the data for those who don't practice sports in relation to those who do. In the comparison between the sexes, it was verified for female sex in anger state subscale a significant difference and for male sex anger trait and reaction subscale. It shows that boys who play sports have a larger anger trait and react to more situations of anger than those who don't practice them, which refers to the comparison with groups composed by sex, age and the fact whether they practice sports or not. The age 14 was verified with a larger number of significant comparisons before ages 15 and 16 for anger expression as state and trait. In the comparison of motor performance of those who practice and also those who don't practice sports all somatomotor variables of physical aptitude for sport performance was statistically significant for the ones who practice sports. What refers to gender, in all tests applied in schools, the male and female sport players are significantly different in relation to the others who do not play sports. In comparison with the median values of the tests of those who practice and those who don't practice sports, the male sex indicates better results than the female one. Among the ages that were observed, the one which got more expressive results in comparisons was the age 15 and the one which had smaller dimension was age 14, resulting significant differences in relation to age. So what refers to anger expression as trait and motor performance, the sports practitioner obtained expressive data in relation to non- practitioners, exposing the search for further study in this area and the monitoring of professionals who work with this age group.